2013
DOI: 10.1371/journal.pone.0060872
|View full text |Cite
|
Sign up to set email alerts
|

A Population Based Study of Seasonality of Skin and Soft Tissue Infections: Implications for the Spread of CA-MRSA

Abstract: Methicillin resistant Staphylococcus aureus (MRSA) is currently a major cause of skin and soft tissue infections (SSTI) in the United States. Seasonal variation of MRSA infections in hospital settings has been widely observed. However, systematic time-series analysis of incidence data is desirable to understand the seasonality of community acquired (CA)-MRSA infections at the population level. In this paper, using data on monthly SSTI incidence in children aged 0–19 years and enrolled in Medicaid in Maricopa C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 31 publications
1
37
0
Order By: Relevance
“…Specifically, investigators have found a statistically significant correlation between both temperature and humidity and S. aureus skin and soft-tissue infections. 36 McBride et al found that S. aureus bacterial populations on the skin are significantly higher during warm and humid months. 28 Skin-to-skin contact, which plays a large role in the nosocomial transmission of S. aureus , increases in frequency during the late summer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, investigators have found a statistically significant correlation between both temperature and humidity and S. aureus skin and soft-tissue infections. 36 McBride et al found that S. aureus bacterial populations on the skin are significantly higher during warm and humid months. 28 Skin-to-skin contact, which plays a large role in the nosocomial transmission of S. aureus , increases in frequency during the late summer.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a recent time series analysis of 51,287 pediatric skin and soft-tissue infection clinical encounters found that rates of S. aureus infection were highest in the summer months. 36 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, degradation of host-or SAK-promoted fibrin clots could help bacteria to spread (37). Damage to subcutaneous tissue could contribute to the pathogenesis of skin soft tissue infections caused by CA-MRSA (38). Degradation of opsonins could contribute to the avoidance of neutrophil-mediated phagocytosis and killing (20 -22).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a recent time series analysis of 51,287 pediatric skin and soft-tissue infection clinical encounters found that rates of S. aureus infection were highest in the summer months. 22 In addition, Mermel et al 23 determined that seasonal variation of S. aureus , specifically community-acquired methicillin-resistant S. aureus , occurred in both adult and pediatric populations. Peritonitis infections involving coagulase-negative Staphylococcus also appear to be more common during the spring and summer.…”
Section: Discussionmentioning
confidence: 99%